2018
DOI: 10.1016/j.redox.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-specific inactivation of LPP3 in mice leads to myocardial dysfunction and heart failure

Abstract: Lipid Phosphate phosphatase 3 (LPP3), encoded by the Plpp3 gene, is an enzyme that dephosphorylates the bioactive lipid mediator lysophosphatidic acid (LPA). To study the role of LPP3 in the myocardium, we generated a cardiac specific Plpp3 deficient mouse strain. Although these mice were viable at birth in contrast to global Plpp3 knockout mice, they showed increased mortality ~ 8 months. LPP3 deficient mice had enlarged hearts with reduced left ventricular performance as seen by echocardiography. Cardiac spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 29 publications
3
66
0
1
Order By: Relevance
“…Lipid phosphate phosphatase 3 (LPP3), is a major enzyme that dephosphorylates LPA. Cardiac-specific inactivation of LPP3 displays cardiac hypertrophy and myocardial dysfunction in mice, indicating that the LPA/LPP3-signaling play an important role in normal function of cardiomyocytes ( Chandra et al, 2018 ). These data indirectly support the findings in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid phosphate phosphatase 3 (LPP3), is a major enzyme that dephosphorylates LPA. Cardiac-specific inactivation of LPP3 displays cardiac hypertrophy and myocardial dysfunction in mice, indicating that the LPA/LPP3-signaling play an important role in normal function of cardiomyocytes ( Chandra et al, 2018 ). These data indirectly support the findings in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial oxygen consumption rate was measured with an XF24 Extracellular Flux Analyzer (Seahorse Biosciences, North Billerica, MA) by methods as described previously 22, 23, 24. Heart mitochondria were isolated using MS‐EGTA buffer (225 mmol/L mannitol, 75 mmol/L sucrose, 5 mmol/L HEPES, and 1 mmol/L EGTA, pH 7.4) by differential centrifugation as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Among the 14 genes that were commonly down-regulated in all three mutants, four belonged to green (nid1b, papss2b, vcanb, bmp3) and two to salmon (plppr3a, spon1b) modules. Genes including vcan, plppr3a, and Bmp family were previously found to play a crucial role in heart morphogenesis and function (Marques and Yelon 2009;Kern et al 2010;Chandra et al 2018). Similarly, comparing chromatin accessibility data revealed that 21% (73 regions), 24% (13 regions), and 29% (five regions) of proximal NFRs that showed decreased acces-sibility in gata5 tm236a/tm236a , hand2 s6/s6 , and tbx5a m21/ m21 mutants were located within the proximal promoters of genes belonging to cardiac modules (Fig.…”
Section: Disruption Of Cardiac Tfs Affects Regulatory Network Drivinmentioning
confidence: 99%